Chemical constituents from theleaves of Uvaria bonianain Vietnam - Tam, Nguyen Thanh; Tuan, Nguyen Ngoc; Trung, Hoang Van; My Chau, Le Thi; Trung Anh, Dinh Thi; Luu, Hoang Van (Vietnam Journal of Science and Technology, 2019)
Abstract HCTN_12 A phytochemical study of extracts of Uvaria boniana Fin. & Gagnep collected at Vũ Quang National park, Nghe An province leaves led to the isolation of five secondary metabolites, including uvaridacol G (1); 4-methyl-4-[(2Z)-3’-phenylprop-2’-en-1’-yl]cyclohex-2-en-1-one (2); 3,7- dimethoxy quercetin 4’- O- [α-L- rhamnopyranosyl-(12) -β-D- glucopyranoside (3); b-sitosterol (4) and stigmasterol (5). Their structure elucidation were determined on the basis of one and two-dimensional NMR and spectrometric methods in combination with molecular modeling. This is the first report on the chemical constituents of Vietnamese Uvaria boniana.